2017
DOI: 10.3945/an.117.015560
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Effects of Polyols on Gastrointestinal Health and Irritable Bowel Syndrome

Abstract: Polyols are sugar alcohols found in certain fruits, vegetables, and sugar-free sweeteners. They make up a component of the diet low in fermentable oligosaccharides, disaccharides, monosaccharides, and polyols, which is gaining popularity in the treatment of patients with irritable bowel syndrome (IBS). We conducted a systematic review to evaluate the effects of polyols on the gastrointestinal tract in healthy men and women and in patients with IBS. Utilizing PubMed, Ovid, and Embase databases, we conducted a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(56 citation statements)
references
References 75 publications
(103 reference statements)
1
46
0
1
Order By: Relevance
“…RdINV also used different alditols as fructosylation acceptors, including erythritol and mannitol, which could improve their functional properties. These low-digestible molecules are considered a food supplement for people with diabetes and intestinal disorders, but they also could increase the bifidobacteria community in the human gut microbiome [46,47]. Therefore, the broad acceptor promiscuity of RdINV would increase its biotechnological potential and make it interesting for food and pharmacological sectors.…”
Section: Discussionmentioning
confidence: 99%
“…RdINV also used different alditols as fructosylation acceptors, including erythritol and mannitol, which could improve their functional properties. These low-digestible molecules are considered a food supplement for people with diabetes and intestinal disorders, but they also could increase the bifidobacteria community in the human gut microbiome [46,47]. Therefore, the broad acceptor promiscuity of RdINV would increase its biotechnological potential and make it interesting for food and pharmacological sectors.…”
Section: Discussionmentioning
confidence: 99%
“…The most important congenital risk factors include age, genotypes (genetic factors), gender, and race. The second group includes variable determinants, i.e., improper oral hygiene, local factors of plaque accumulation (gingival areas, inadequately placed fillings, tooth crowding, cervical areas of crowns, bridges), unfavorable composition of bacterial biofilm present on the teeth, use of tobacco (smoking pipes, cigarettes, cigars, the use of non-flammable tobacco-chewing snuff), nutritional deficiencies (lack of vitamin C, calcium), diseases (e.g., diabetes, alcoholism, osteoporosis) and long-term exposure to stressors [ 113 , 114 , 115 , 116 , 117 , 118 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 ],…”
Section: Discussionmentioning
confidence: 99%
“…Intensive sweeteners, weaker than sucrose, should meet certain conditions, i.e., have sweetness such as sucrose, be safe for health, be cheap and functional, demonstrate resistance to digestive processes in the digestive tract, not they should provide energy and cause tooth decay, allergies and diarrhea. Intensive sweeteners are divided into natural (stevidosis, glycyrhizin, thaumatin, monellin, pentadine, curculin-in Poland only thaumatin is approved for use in food) and artificial (saccharin, aspartame, acesulfame K, cyclamates, alitama, sucralose) [ 125 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 , 174 , 175 , 176 , 177 , 178 , 179 , 180 ].…”
Section: Diet—the Basis Of Human Health and Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, ingestion of these poorly-absorbed sugar alcohols may lead to gastrointestinal symptoms in some people and have laxative effects. For example, it has been reported that the excessive use of chewing gum containing sorbitol may cause symptoms such as diarrhea, weight loss, and bloating [4,5]. The main cause of the diarrhea is thought to be the accumulation of poorly-absorbed sugar alcohols in the colon, where they increase colonic osmotic pressure and prevent water absorption [6].…”
Section: Introductionmentioning
confidence: 99%